Aggregated motion estimation for real‐time MRI reconstruction. Issue 4 (18th November 2013) - Li, Housen; Haltmeier, Markus; Zhang, Shuo; Frahm, Jens; Munk, Axel
<x xml:space="preserve">Abstract</x> Purpose In real‐time MRI serial images are generally reconstructed from highly undersampled datasets as the iterative solutions of an inverse problem. While practical realizations based on regularized nonlinear inversion (NLINV) have hitherto been surprisingly successful, strong assumptions about the continuity of image features may affect the temporal fidelity of the estimated reconstructions. Theory and Methods The proposed method for real‐time image reconstruction integrates the deformations between nearby frames into the data consistency term of the inverse problem. The aggregated motion estimation (AME) is not required to be affine or rigid and does not need additional measurements. Moreover, it handles multi‐channel MRI data by simultaneously determining the image and its coil sensitivity profiles in a nonlinear formulation which also adapts to non‐Cartesian (e.g., radial) sampling schemes. The new method was evaluated for real‐time MRI studies using highly undersampled radial gradient‐echo sequences. Results AME reconstructions for a motion phantom with controlled speed as well as for measurements of human heart and tongue movements demonstrate improved temporal fidelity and reduced residual undersampling artifacts when compared with NLINV reconstructions without motion estimation. Conclusion Nonlinear inverse reconstructions with aggregated motion estimation offer improved image quality and temporal acuity for visualizing rapid dynamic processes by real‐time MRI. Magn Reson Med 72:1039–1048, 2014. © 2013 Wiley Periodicals, Inc.